The Helicobacter pylori orphan ATTAAT-specific methyltransferase M.Hpy99XIX plays a central role in the coordinated regulation of genes involved in iron metabolism - Wilhelm Gottschall; Florent Ailloud; Christine Josenhans; Sebastian Suerbaum (mBio)
ABSTRACT Helicobacter pylori genomes contain a large and variable portfolio of methyltransferases (MTases), creating a highly diverse methylome. Here, we characterize a highly conserved ATTAAT-specific MTase, M.Hpy99XIX (H. pylori strain J99, alternative designations in other strains, M.HpyAVII and M.HpyPVII), the only H. pylori MTase never associated with an endonuclease (“orphan” MTase). Inactivation of M.Hpy99XIX resulted in a significant change in the transcription of >100 genes, despite the fact that only a small subset of their promoter regions contained an ATTAAT target motif. Patterns of transcriptional change showed significant correlations with changes reported for H. pylori mutants in the regulators involved in iron regulation. MTase inactivation also caused a higher susceptibility to diverse metal ions as well as iron chelation and oxidative stress. These phenotypes could be traced back to the methylation of single motifs in the promoter regions of iron transporters frpB1 and fecA1. Altogether, methylation of individual motifs in promoters can have a large downstream effect, causing major changes to metabolic pathways. These findings suggest that the methylome represents a universal and dynamic interface connecting genome diversity and transcriptional regulation. Very recently, a new ecospecies of H. pylori, Hardy, has been reported. M.Hpy99XIX is present in the majority of “normal” (Ubiquitous) H. pylori strains, whereas no single Hardy strain contained this gene, consistent with other reported differences between Hardy and Ubiquitous strains related to iron/metal homeostasis. ATTAAT methylation is intricately connected with the bacterial transcriptional network, highlighting the important role of bacterial epigenetic modifications in bacterial physiology and pathogenesis.IMPORTANCEHelicobacter pylori has one of the largest repertoires of methyltransferases. Methylation has been associated with multiple functions in H. pylori, including the defense against foreign DNA and transcriptional regulation. Regulation of gene expression by methylation has the potential to influence many distant genes across the genome via target motifs in proximity to transcription start sites. Here, we sought to understand the role of M.Hpy99XIX, an orphan methyltransferase targeting the ATTAAT motif that is highly conserved in H. pylori. We show that by directly regulating specific genes involved in iron uptake via methylated ATTAAT motifs, M.Hpy99XIX has a significant effect on iron homeostasis by triggering the canonical iron regulatory pathway. Furthermore, we show that M.Hpy99XIX appears to have been acquired after the split between the two ecospecies of H. pylori, suggesting that its role in the tuning of iron homeostasis might have contributed to this divergence.